Efektivitas Pelayanan Keluarga Berencana Pada Masa Pandemi Covid-19 Di Puskesmas Sentosa Baru Kecamatan Medan Perjuangan Kota Medan - Atikah Dwi Ramadhani; Adam Adam; Beby Masitho Batubara (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2022)
This study aims to find out how effective the service is and the inhibiting factors for family planning services at the Sentosa Baru Public Health Center, Medan Struggle District, Medan City. With the increasing number of COVID-19 cases in Indonesia, the government has implemented a large-scale social restriction policy (PSBB), this has an impact on family planning services at the new Sentosa Health Center. In this study using a qualitative approach using interviews, observation and documentation. The results of this study indicate that family planning services at the Sentosa Baru Health Center have not been running effectively with a decrease in active family planning participants in 2020 and the cessation of direct socialization to the community and the emergence of public fear of visiting the puskesmas making the success of the program's objectives not run properly. The inhibiting factors in the effectiveness of family planning services at the Sentosa Baru Health Center are the limitations of family planning services and the cessation of outreach to the community and the lack of service facilities and infrastructure during the COVID-19 pandemic so that monitoring of family planning service program activities cannot run optimally, this will have an impact on a decrease in active family planning users at the new sentosa health center in 2020.